A comparative analysis of adiponectin and soluble CD36 levels between diabetic and non-diabetic metabolic syndrome patients - Khan, Mansura; Alam, M. Sohrab; Siddiquee, Nadia; Nur, Jesmin; Rahman, Zeenat Farzana; Moniruzzaman, Mohammad (International Journal of Research in Medical Sciences, 2024)
Background: Metabolic syndrome refers to a constellation of interrelated metabolic risk factors that promote the development of type-2 diabetes mellitus (T2 DM) and cardiovascular diseases (CVD). The purpose of this study was to compare the serum levels of adiponectin and soluble CD36 between diabetic and non-diabetic metabolic syndrome patients. The aim of this study was to compare the serum levels of adiponectin and soluble CD36 between diabetic and non-diabetic metabolic syndrome patients. Methods: This cross-sectional analytical study, conducted at the Outpatient Department and Department of Immunology at BIRDEM General Hospital over 12 months, included 80 participants: 60 with metabolic syndrome (30 type-2 diabetic and 30 non-diabetic) and 20 healthy controls. Participants underwent clinical examinations, anthropometric measurements and blood tests for serum analysis of adiponectin and soluble CD36 using ELISA and immunonephelometry. Data were analyzed using nonparametric tests (Mann-Whitney U test, Levene’s test) and correlation analyses (Pearson and Spearman) with p<0.05, using SPSS version 20. Results: Metabolic syndrome patients had higher weight, BMI, waist circumference and blood pressure compared to healthy subjects. Adiponectin and soluble CD36 levels were significantly lower in metabolic syndrome patients, with differences between diabetic and non-diabetic groups. Adiponectin negatively correlated with waist circumference, blood pressure and triglycerides, while soluble CD36 positively correlated with waist circumference, diastolic blood pressure and triglycerides. Conclusions: In conclusion, our study highlights that adiponectin and soluble CD36 levels are significantly altered in diabetic versus non-diabetic metabolic syndrome patients, suggesting their potential as biomarkers for metabolic syndrome.